THE ROLE OF PROTEIN KINASE A IN VIOLATION OF PLATELET AGGREGATON AMONG PATIENTS WITH GASTRODUODENAL ULCER BLEEDING - Делій, В.Ю. (World of Medicine and Biology, 2015)
Typical violations of platelets response to aggregation inductors and adhesive molecules are prolonged activation and reversible aggregation that greatly affect the outcome of disease. In our previous study it has been shown that bleeding recurrence is observed among patients with these violations even if platelets response reaches medium and high level. This fact clearly indicates that one of the reasons of unstable hemostasis and probable cause of bleeding recurrence among these patients are violations that occur in platelets intracellular signaling system. It is known that protein kinase A is a regulator of energy balance of platelets and plays a significant role in the implementation of their response. In this research we have tried to investigate whether platelet’s protein kinase A dysfunction takes place among patients with gustroduodenal bleeding, and if so, whether this dysfunction influences on platelet response to aggregation inductors and adhesive molecules, and whether protein kinase. A dysfunction affects endoscopy characteristics of hemostasis. For this, we have examined platelet aggregation induced by ADP with or without protein kinase A inhibitor. Measurement of platelet aggregation was carried out by spectrophotometry. Inductors were used in EC50, namely ADP 50 µM/l. In order to assess the protein kinase A state its inhibitor, tolbutamide, was used in concentration 200 µM/l.